2008
DOI: 10.1093/sleep/31.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Heart Rate Recovery Following Exercise Testing in Overweight Young Men with Untreated Obstructive Sleep Apnea

Abstract: We found that OSA elicits alterations in the cardiovascular response post exercise, reflected by an attenuated HR recovery. This may indicate an imbalance in the autonomic regulation of HR. Exercise tests may provide utility in risk stratification for those at risk for OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
51
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 36 publications
7
51
2
2
Order By: Relevance
“…In a cohort of morbidly obese patients, Vanhecke et al [7] found that those with OSA had slower HRR than those without. Similarly, Hargens et al [8] demonstrated that overweight young men with OSA had significantly slower HRR than men with similar body mass index but without OSA and men with normal weight and without OSA. Thus, the results of these studies were overall consistent.…”
mentioning
confidence: 89%
“…In a cohort of morbidly obese patients, Vanhecke et al [7] found that those with OSA had slower HRR than those without. Similarly, Hargens et al [8] demonstrated that overweight young men with OSA had significantly slower HRR than men with similar body mass index but without OSA and men with normal weight and without OSA. Thus, the results of these studies were overall consistent.…”
mentioning
confidence: 89%
“…The impact of obstructive sleep apnoea (OSA) on exercise capacity remains unclear, given some studies have shown that this disorder reduces exercise capacity (2-6), whereas others have found no differences in exercise capacity OSA populations (7)(8)(9)(10)(11)(12). factors impact aerobic capacity, as measured by cardiopulmonary exercise testing (CPET).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Furthermore, only one study has included CPET measurements obtained A delayed heart rate (HR) recovery after CPET is considered a predictor of overall mortality (16). Some studies have shown that patients with OSA have an ttenuated HR recovery that is dependent on OSA severity (3,5,11,17). A possible mechanism involves reduced parasympathetic activity, which is observed in patients with OSA during the recovery phase of exercise (11).…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations